EFFECT OF SOME ENVIRONMENTAL FACTORS ON WEIGHTS LOSING OF DIFFERENT STAGES OF PORCELLIO SPINICORNISISOPODA : PORCELLIONIDAEIN AL- JADRIYA REGION/ BAGHDAD – IRAQ - Hassan, Suad (Iraqi Journal of Science, 2024)
The present study concerned with the effect of some environmental factors (humidity and temperture) on weight losing of manca, Juvenales and adult of crustacean Isopoda Porcellio spinicornis under 37oc and 60% -70% humiditity in the laboratory and during the period from April ( 2007- 2008 ) in field .The study showed that the weights of manca developed to females were higher than of those developed to males , the highest loss in weights of manca developed to adults under field conditions were at the means of (2.3, 2.2 , 2.5)mg during June, July and August respectively.